Continuous hydrogen production with anaerobic palm oil mill effluent (POME) sludge immobilized synthetic polymer - Fairuz, Rosni (2012)
Hydrogen has been recognized as a promising energy in the future for being clean, efficient and recyclable. Therefore, it can be replaced with other non-renewable energy such as coal, gasoline, petroleum and metal cores for energy. The increasing of the palm oil processing has resulted the increasing of the Palm Oil Mill Effluent (POME) that can't be treated for drinking water and can lead to an increase the total waste water in Malaysia. The feasibility of hydrogen generation from palm oil mill effluent (POME), a high strength wastewater with high solid content, was evaluated in an upflow anaerobic sequencing batch reactor (UASBR). Most studies for the hydrogen production in the applied cell suspension systems often encountered problem with biomass washout at high dilution rates and required recycling of biomass from the effluent to maintain sufficient cell density for continuous hydrogen production. This study is needed to determine the effect of hydraulic retention time (HRT) of the immobilized Upflow Anaerobic Sludge Blanket (UASB) reactor to the quality of the POME and to characterize the POME properties in terms of the COD, TSS and VSS before and after the sample is being treated. Four different hydraulic retention times (HRT), ranging from 4 h to 16 h at constant temperature of were tested to evaluate hydrogen productivity and operational stability of immobilized UASBR. The results showed higher system efficiency was achieved at 1-IRT of 2 h with maximum hydrogen production rate of 330 mL-H 2IhIL and hydrogen yield of 0.33 mol-H 2 /mol-sucrose. COD removal reached more 50%, respectively. Butyrate was found to be the dominant metabolite in all FIRTs. Low concentration of volatile fatty acid (VFA) confirmed the state of stability and efficiency of the operation was achieved in immobilized UASBR. 35°C